Penyelesaian Perselisihan Upah Dalam Hubungan Industrial di Indonesia Berdasarkan Undang-undang 13 Tahun 2003 Tentang Ketenagakerjaan dan Undang-undang Nomor 6 Tahun 2023 Tentang Cipta Kerja - Andri Sunandar; Boidoon Sinambela; Angga Rizkia; Andri Herman Setiawan (Journal of Innovative and Creativity, 2025)
Wage disputes constitute the most prevalent category of industrial relations conflicts in Indonesia, emerging from discrepancies between minimum wage compliance, interpretation of wage structures and scales, elimination or reduction of wage components, and violations of the equal pay for equal work principle. This normative legal research employs statutory and conceptual approaches to examine the regulatory frameworks governing wage protection and dispute resolution mechanisms established under Law No. 13 of 2003 concerning Labor and Law No. 6 of 2023 concerning Job Creation. The research analyzes the conceptual foundations of wages within Indonesian legal jurisprudence, encompassing definitions, components, and minimum wage determinations, as well as the legal protections afforded to workers. The findings demonstrate that although both statutory instruments establish comprehensive mechanisms for wage protection including minimum wage provisions, payment procedures, wage components, and sanctions for employer violations implementation remains significantly challenged by employer non-compliance, insufficient enforcement oversight, divergent interpretations of new regulatory provisions between workers and employers, and worker ignorance regarding wage-related rights. The research concludes that achieving effective wage dispute resolution and industrial relations harmony requires strengthening mediation mechanisms, enhancing wage-setting transparency, ensuring consistent law enforcement, intensifying government labor supervision, and fostering active participation of labor unions to ultimately secure sustainable protection of workers' wage rights in Indonesia's industrial relations landscape.